Relationship between Febrile Seizures and the Incidence of Microcytic Hypochromic Anemia in Children at Sanjiwani General Hospital, Gianyar, Indonesia - I Dewa Ayu Agung Diah Sutarini; Romy Windiyanto (HM Publisher, 2023)
Background: Febrile seizures are the most common seizures in children. As many as 2% to 5% of children aged less than 5 years have had seizures accompanied by fever, and most occurrences are at the age of 17-23 months. Microcytic hypochromic anemia causes hypoxic conditions and neuronal instability due to iron depletion. This study aimed to explore the relationship between febrile seizures and the incidence of microcytic hypochromic anemia in children at Sanjiwani General Hospital, Gianyar, Indonesia. Methods: This study was an analytic observational study with a cross-sectional approach. A total of 59 subjects participated in this study. Data analysis was carried out with the help of SPSS software in univariate and bivariate to determine the relationship between febrile seizures and microcytic hypochromic anemia. Results: There is a relationship between the incidence of febrile seizures and the incidence of microcytic hypochromic anemia, with p<0.05. This study also showed that the risk of febrile seizures increased 1.7 times higher in individuals with microcytic hypochromic anemia. Conclusion: There is a relationship between the incidence of febrile seizures and the incidence of microcytic hypochromic anemia in pediatric patients at Sanjiwani General Hospital, Gianyar, Indonesia.